2005
DOI: 10.1620/tjem.207.263
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brachial-Ankle Pulse Wave Velocity in Japanese and Russians

Abstract: Pulse wave velocity (PWV) is a well-known indicator of arterial stiffness and a marker of the presence of vascular lesions. Cardiovascular mortality in Russia has become the highest in the world. The Japanese are enjoying long lives, and the mortality caused by cardiovascular diseases has thus far remained at lower levels than that in Russia. In this study, we focused on brachial-ankle pulse wave velocity (baPWV) obtained from normal human subjects in Russia as well as in Japan, and compared their respective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
(31 reference statements)
3
16
1
1
Order By: Relevance
“…Although the Russian subjects had higher HR and BP levels, these levels were independent of the differences in the CAVI among the two populations. While this is the first report using the CAVI for healthy younger Russian people, a previous study, which used the brachial-ankle pulse wave velocity (baPWV: an indicator of arterial stiffness), showed that healthy Russian individuals might have higher arterial stiffness values compared to their Japanese counterparts 21) . In that report, the authors simply described the findings in Russian subjects under 39 years of age 21) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the Russian subjects had higher HR and BP levels, these levels were independent of the differences in the CAVI among the two populations. While this is the first report using the CAVI for healthy younger Russian people, a previous study, which used the brachial-ankle pulse wave velocity (baPWV: an indicator of arterial stiffness), showed that healthy Russian individuals might have higher arterial stiffness values compared to their Japanese counterparts 21) . In that report, the authors simply described the findings in Russian subjects under 39 years of age 21) .…”
Section: Discussionmentioning
confidence: 88%
“…While this is the first report using the CAVI for healthy younger Russian people, a previous study, which used the brachial-ankle pulse wave velocity (baPWV: an indicator of arterial stiffness), showed that healthy Russian individuals might have higher arterial stiffness values compared to their Japanese counterparts 21) . In that report, the authors simply described the findings in Russian subjects under 39 years of age 21) . Additionally, some differences are known to exist between the baPWV and the CAVI levels, because the CAVI has less dependence on the BP 11,13) .…”
Section: Discussionmentioning
confidence: 88%
“…After at least a 5-minute bed rest, baPWV was recorded using an automated device (VaSeraVS-1000, Fukuda Denshi, Tokyo) (Liu et al 2005;Watanabe et al 2005). This device simultaneously records baPWV, blood pressure (BP), electrocardiogram, and heart sounds.…”
Section: Measurement Of Bapwvmentioning
confidence: 99%
“…This instrument simultaneously records the baPWV on the left and right sides. The highest baPWV on both sides was determined, and subsequent statistical analyses were performed using these values (Liu et al 2005;Tomiyama et al 2005).…”
Section: Measurement Of Bapwvmentioning
confidence: 99%
“…It is well known that arterial stiffness detected via an increase in pulse wave velocity predicts an increased risk of cardiovascular events in patients with essential hypertension (Liu et al 2005;Liu et al 2006). Recently, the cardio-ankle vascular index (CAVI) has been used to assess arterial stiffening instead of pulse wave velocity because it is less influenced by blood pressure than pulse wave velocity (Yambe et al 2004;Yambe et al 2005;Shirai et al 2006).…”
mentioning
confidence: 99%